From the grabbing hand to the helping hand: A rent seeking model of China's township-village enterprises - Jiahua Che (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
I present a study of ownership of firms under government rent seeking. Using its control of regulated inputs, a government agency extracts rents from a manager who undertakes an investment. Such a government rent seeking activity leads to a typical hold-up problem. Government ownership is shown to serve as a second best commitment mechanism through which the government agency will restrain itself from the rent seeking activity and even offer the manager support and favor such as tax breaks and subsidies. This mechanism works at a cost as government ownership compromises ex post managerial incentives and creates distortion in resource allocation. Nevertheless, government ownership may Pareto dominate private ownership under certain conditions. These conditions correspond to a host of stylized empirical observations concerning local government-owned firms (township-village enterprises) during China's transition to a market economy.
Keywords: D23; D72; L33; 330; ownership of firms; government; rent seeking; township and village enterprises; China; Rent Seeking; Eigentum; Öffentliches Unternehmen; Ländliches Kleingewerbe; China